Análise da incidência de comorbidades em pacientes com câncer de boca e orofaringe e sua associação com as variáveis clinicopatológicas e sobrevida - Curvo, Ana Raphaela Maia Dezan Couto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the incidence of comorbidities in paientes with squamous cell carcinoma (OSCC) and oropharynx and its association with clinical and survival variables. We retrospectively reviewed the records of patients with head and neck cancer treated at the Oral Oncology Center (COB) Araçatuba School of Dentistry - FOA between 1991 and 2013. The univariate analyzes were used to evaluate the association between the presence of comorbidities and clinical variables and Kaplan-Meier test to verify the association with the global and specific survival. The study included 473 patients with squamous cell carcinoma of the mouth and oropharynx. Of all patients, 44.4% had a history of some type of comorbidity. The most common comorbidity in cancer patients was hypertension, followed gastritis, diabetes, stroke and pulmonary emphysema. There was a higher incidence of co-morbidities patients and in women over 65 years. The presence of comorbidities was also associated with clinical staging and size of the initial primary tumor (T1 / T2). There was no association of the occurrence of comorbidities with a history of smoking and alcohol abuse, presence of regional metastasis, histological grade of the primary tumor and the occurrence of recurrence and second primary tumor. There was no association between the presence of comorbidity and the overall and specific survival of patients with squamous cell carcinoma of the mouth and oropharynx. When the occurrence of hypertension was analyzed as an isolated variable, the results showed that patients with oral squamous cell carcinoma and hypertensive oropharynx also fewer women and older than non-hypertensive patients had early-stage cancer and relapse rates smaller. The presence of hypertension was associated with a higher overall and specific...

O objetivo do presente estudo foi avaliar a incidência de comorbidades em paientes com carcinoma espinocelular(CEC)de boca e orofaringe e sua associação com as variáveis clinicopatológicas e sobrevida. Foram analisados retrospectivamente os prontuários clínicos dos pacientes com câncer de cabeça e pescoço atendidos no Centro de Oncologia Bucal (COB) da Faculdade de Odontologia de Araçatuba - FOA, entre 1991 e 2013. Foram utilizadas análises univariadas para avaliar a associação entre a presença de comorbidades e as variáveis clinicopatológicas e teste de Kaplan-Meier para verificar a associação com a sobrevida global e específica. Foram incluídos no estudo 473 pacientes com CEC de boca e orofaringe. Do total dos pacientes, 44,4% apresentavam histórico de algum tipo comorbidade. A comorbidade mais frequente nos pacientes oncológicos foia hipertensão arterial, seguida de gastrite, diabetes, acidente vascular cerebral e enfisema pulmonar. Houve maior incidência de comorbidades em mulheres e pacientes acima dos 65 anos. A ocorrência de comorbidades também foi associada ao estadiamento clínico e tamanho do tumor primário inicial (T1/T2). Não foi observada associação da ocorrência de comorbidades com o histórico de tabagismo e alcoolismo, presença de metástase regional, grau histopatológico do tumor primário e ocorrência de recidiva e segundo tumor primário. Não houve associação entre a presença de comorbidade e a sobrevida global e específica dos pacientes com CEC de boca e orofaringe. Quando a ocorrência de hipertensão arterial foi analisada como variável isolada, os resultados mostraram que os pacientes com CEC de boca e orofaringe hipertensos também eram em maior número mulheres e mais velhos do que os pacientes não hipertensos e apresentavam o câncer em estágio mais inicial...
Keywords: Neoplasias bucais; Neoplasias orofaríngeas; Comorbidade; Mouth neoplasms